Nasyr Da‘watu al-Tasawwuf sl-Ijtimā‘ī li Mukāfahati sl-Irhāb wa al-Tatarruf - Rizqa Ahmadi (UIN Sunan Kalijaga Yogyakarta, 2017)
Terrorism and radicalism are arguably against religion, law, and human nature. None of the religions on this earth encourage both actions. Whenever those doctrines are found and spread, it must be coming from a corrupt source. Terrorism and extremism are necessary and urgent issues. Both have become the enemy of all government in the world. The governments have tried to resist and fight against it in several ways and methods, but this case is still continued until our time now but grew and prospered. Based on this recent situation, this research reveals an issue, i.e. how Social Mysticism (al-Tasawuf al-Ijtima’i) and its characteristics became an approach to fighting terrorism and radicalism. Social Mysticism is an applicative formula for the teachings of mysticism and Sufism. This kind of mysticism teaches humanism value that elevates the dignity of human being. Social mysticism teaches tolerance and compassion among people, whatever their religion and their beliefs. It is in contrary to the thought of the terrorist and takfiri group that called to rigorism, violence, and bombing in the name of religion. Social mysticism gives an example through practical ways, e.g. moral of being noble, altruism and friendship. These morals are key in establishing a proper civil society.